Structures and Biological Activities of Secondary Metabolites from Trichoderma harzianum - Rui Guo; Gang Li; Zhao Zhang; Xiaoping Peng (Marine Drugs, 2022)
The biocontrol fungus Trichoderma harzianum, from both marine and terrestrial environments, has attracted considerable attention. T. harzianum has a tremendous potential to produce a variety of bioactive secondary metabolites (SMs), which are an important source of new herbicides and antibiotics. This review prioritizes the SMs of T. harzianum from 1988 to June 2022, and their relevant biological activities. Marine-derived SMs, especially terpenoids, polyketides, and macrolides compounds, occupy a significant proportion of natural products from T. harzianum, deserving more of our attention.